Tax Mapping Based on Klassen Typology: A Case Study of Central Lombok - Agustiani, Eka; Astuti, Endang; Aprianti, Vina (West Science Journal Economic and Entrepreneurship, 2025)
This research aims to analyze the potential for regional tax revenue in increasing Regional Original Income (PAD) in Central Lombok Regency in 2017-2023. This research uses a quantitative descriptive approach. The data analysis technique in this research is analysis of regional tax revenue reports using the Klassen Typology method. The results of the research show that using the Klassen Typology method, the types of taxes included in the Prime/Excellent sector are taxes, namely hotel tax, restaurant tax, advertising tax, street lighting tax, parking tax, rural and urban land and building tax and title acquisition tax. on Soil and Rocks. The type of tax included in the Potential sector is Non-Metal Mineral and Rock tax. The types of taxes included in the Developing sector are entertainment tax and ground water tax. Then the type of tax that is included in the Underdeveloped sector is the Swallow's Nest Tax.